Hypoxia Mimetic Agents for Ischemic Stroke - Davis, Charles K.; Jain, Saurabh A.; Bae, Ok-Nam; Majid, Arshad; Rajanikant, G. K. (Frontiers in Cell and Developmental Biology, 2019)
Every year stroke claims more than 6 million lives worldwide. The majority of them are ischemic strokes. Small molecule-based therapeutics for ischemic stroke have attracted a lot of attention but none has been shown to be effective clinically so far. Hypoxia-inducible factor-1 (HIF-1) plays a crucial role in the transcriptional adaptation of cells to hypoxia. Small molecule-based hypoxia-mimetic agents inhibit HIF-prolyl hydroxylases (PHDs), stabilize HIF-1α and have been shown to confer ischemic neuroprotection. These agents are mainly classified into iron chelators, iron competitors, and 2 oxoglutarate (2OG) analogs. This review discusses HIF structure and key players in the HIF degradation pathway as well as the genes, proteins and chemical molecules that are connected to HIF-1 and how they affect cell survival following ischemic injury. Furthermore, this review gives a summary of studies that used PHD inhibitors as hypoxia mimetic agents for the treatment of ischemic injury.